Perspectives on the Concepts of 'Records' and 'Archives' in Thailand and the Current Roles of National Archives of Thailand (NAT) - Poolsatitiwat, Waraporn (Humanities, Arts and Social Sciences Studies, 2020)
An exploration of the definitions of ‘record’ and ‘archive’ in Thailand identifies not only the lack of integration of records and archives but also the Thai perception of archives as memory and heritage. This perspective determines the role of the National Archives of Thailand (NAT) to acquire, appraise, arrange, preserve, conserve, and provide access to archives in its holding. The law requires that non-current records of Thai public agencies be transferred to NAT and have their historical value appraised. In addition, under the National Archives Act of Thailand B.E. 2556 (A.D. 2013), NAT is required to record significant national events and oral history. The legal authority to manage public records belongs to the public agencies who own them. However, under the Office of the Prime Minister’s Regulations on Records Management B.E. 2526 (A.D. 1983), No.2 B.E. 2548 (A.D. 2005), and No.3 B.E. 2562 (A.D. 2019), their authority to establish and manage records is overseen by the Office of the Prime Minister (OPM). The separation of authority for managing records and archives in Thailand plays a significant role in the functions of NAT. First, to ensure that non-current records are effectively transferred, NAT should collaborate with the OPM to develop guidelines to help Thai public agencies properly implement their record management systems. Second, to claim the records of significant national events and oral history as archives, NAT should develop national standards on how to collect, appraise, arrange, and provide access to them. Finally, the key requirement is that archives be recognised as both non-current records and reliable cultural heritage information in accordance with modern archival theories incorporating two archival paradigms: (1) evidence and (2) memory and heritage.